2016
DOI: 10.1177/1073858415601369
|View full text |Cite
|
Sign up to set email alerts
|

The Insula

Abstract: The insula, a ‘cortical hub’ buried within the lateral sulcus, is involved in a number of processes including goal-directed cognition, conscious awareness, autonomic regulation, interoception and somatosensation. While some of these processes are well known in the clinical presentation of migraine (i.e., autonomic and somatosensory alterations), other more complex behaviors in migraine, such as conscious awareness and error detection, are less well described. Since the insula processes and relays afferent inpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(58 citation statements)
references
References 270 publications
(392 reference statements)
3
54
0
1
Order By: Relevance
“…However, only the gross anatomy of the brain has been investigated in previous studies (Borsook et al, 2016; Wang et al, 2016). With a deeper understanding of migraine, the accumulated evidence has shown that the functions of different brain sub-regions vary widely, raising new demands, and challenges for future studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, only the gross anatomy of the brain has been investigated in previous studies (Borsook et al, 2016; Wang et al, 2016). With a deeper understanding of migraine, the accumulated evidence has shown that the functions of different brain sub-regions vary widely, raising new demands, and challenges for future studies.…”
Section: Introductionmentioning
confidence: 99%
“…As a “cortical hub,” the insula carries information of dyspnea and has strong connections with neural structures important in processing emotional information [8, 1214]. However, to our knowledge, only one research explored the underpinnings of depression with the method of fMRI in female asthmatic patients, in which depressed asthma (DA) patients showed a decreased spontaneous activity in the right insula [15].…”
Section: Introductionmentioning
confidence: 99%
“…Кроме того, регионы ствола головного мозга, контролирующие деятельность сердечно-сосудистой системы, участвуют в модуляции боли. Все чаще признается роль гипоталамуса и островка в патофизиологии мигрени и контроле автономных путей, необходимых для поддержания необходимого уровня АД [32].…”
Section: взаимосвязь между мигренью и агunclassified